Hakikat Metode Pendidikan Islam Dalam Presefektif Filsafat Pendidikan Islam - Khoirul Bariah Rambe; Ririn Indriani; Wapiatul Khairiah (Jurnal Bintang Pendidikan Indonesia, 2023)
Islamic education has various methods that are used to facilitate achieving learning objectives, this research uses library research research methods from data that already existed before, the principles of educational methods are 4 principles of religion, biology, psychological foundation yesterday sociological Islamic education method has several characteristics that emphasize exemplary values, educational methods in the Koran namely story and lecture methods methods of question and answer discussion and dialogue, awareness methods, methods of giving rewards and punishments, exemplary methods and in the hadith namely exemplary methods, methods of gentleness or compassion , deductive method, parable method, figurative method, question and answer method, repetition method, experimental method, problem solving method, discussion method, praise method, punishment method.